2021
DOI: 10.3389/fphar.2021.690407
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of Tempol Attenuates the Cardiorespiratory Depressant Effects of Fentanyl

Abstract: Fentanyl is a high-potency opioid receptor agonist that elicits profound analgesia and suppression of breathing in humans and animals. To date, there is limited evidence as to whether changes in oxidant stress are important factors in any of the actions of acutely administered fentanyl. This study determined whether the clinically approved superoxide dismutase mimetic, Tempol (4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl), or a potent antioxidant, N-acetyl-L-cysteine methyl ester (L-NACme), modify the cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 61 publications
12
30
0
Order By: Relevance
“…A major finding of the present study was that the intravenous injection of Tempol and especially at a 100 mg/kg dose was able to immediately reverse the pronounced negative effects of a 10 mg/kg intravenous dose of morphine on ABG chemistry, A-a gradient and SpO 2 in the freely-moving rats. These findings complement our earlier report that pretreatment with a 100 mg/kg dose of Tempol markedly blunted the deleterious changes in ABG chemistry, A-a gradient and ventilatory parameters (e.g., frequency of breathing, tidal volume and minute ventilation) elicited by the subsequent injection of fentanyl in isoflurane-anesthetized rats (Baby et al, 2021). The present study did not directly address the mechanisms underlying the ability of Tempol to reverse the negative effects of morphine on ventilatory control processes pertinent to our study, however, the rapid and sustained effects of Tempol on ABG chemistry and SpO 2 along with the relatively transient effects on A-a gradient (improved gas exchange in the lungs of morphine-treated rats) certainly suggests that the primary reason for the improved status of the ABG chemistry is due to the ability of Tempol to increase ventilatory performance (e.g., enhanced minute ventilation and inspiratory drive) in the morphine-treated rats.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…A major finding of the present study was that the intravenous injection of Tempol and especially at a 100 mg/kg dose was able to immediately reverse the pronounced negative effects of a 10 mg/kg intravenous dose of morphine on ABG chemistry, A-a gradient and SpO 2 in the freely-moving rats. These findings complement our earlier report that pretreatment with a 100 mg/kg dose of Tempol markedly blunted the deleterious changes in ABG chemistry, A-a gradient and ventilatory parameters (e.g., frequency of breathing, tidal volume and minute ventilation) elicited by the subsequent injection of fentanyl in isoflurane-anesthetized rats (Baby et al, 2021). The present study did not directly address the mechanisms underlying the ability of Tempol to reverse the negative effects of morphine on ventilatory control processes pertinent to our study, however, the rapid and sustained effects of Tempol on ABG chemistry and SpO 2 along with the relatively transient effects on A-a gradient (improved gas exchange in the lungs of morphine-treated rats) certainly suggests that the primary reason for the improved status of the ABG chemistry is due to the ability of Tempol to increase ventilatory performance (e.g., enhanced minute ventilation and inspiratory drive) in the morphine-treated rats.…”
Section: Discussionsupporting
confidence: 90%
“…In summary, the present study extends our findings regarding the beneficial effects of Tempol against the negative effects of fentanyl on breathing, ABG chemistry and gas-exchange in the lungs, and the potential problems regarding the ability of Tempol to reduce arterial blood pressure (Baby et al, 2021). Previous studies have demonstrated the beneficial effects of Tempol in cell and animal models of neurodegenerative diseases, shock, hypertension, diabetes, ischemia-reperfusion injury, traumatic brain injury, tumororigenesis, chemotherapy-induced neuropathic pain and alopecia (Wilcox and Pearlman, 2008;Wilcox, 2010;Kim et al, 2016;Bernardy et al, 2017;Wang et al, 2018;Afjal et al, 2019;Chiarotto et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations